Rancang Bangun Alat Presensi Fingerprint Berbasis Website Menggunakan NodeMCU Esp8266 Di SMK NU Darussalam - Bangun Setyawan; Ratna Mustika Yasi; Untung Suryadhianto (ZETROEM, 2021)
Abstract - The purpose of designing a website-based fingerprint attendance device using the NodeMCU ESP8266 microcontroller was to utilize digitalization technology that could be a solution to minimize errors or fraud and forgery in the process of recording attendance. Vocational School SMK NU Darussalam Srono was a Vocational School that still applied conventional attendance recording by recording student attendance on the attendance book, so it was urgent to apply computerized recording by apply website-based concepts that were more efficient and facilitated the administrative process. This study used the NodeMCU ESP8266 microcontroller as the control center, the R307 fingerprint sensor and a website-based configuration interface. The process of reporting attendance results were in the form of archive document files that could be downloaded on the website. Based on the implementation of the test, the total average time used to record attendance was 1.2288 seconds while the registration time was 5.496 seconds. Keywords: Attendance System, NodeMCU ESP8266, Website